2022
DOI: 10.3389/fimmu.2022.945516
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis regulator-mediated patterns associated with immune infiltration features and construction of cuproptosis-related signatures to guide immunotherapy

Abstract: BackgroundLiver hepatocellular carcinoma (HCC) is a prevalent cancer that lacks a sufficiently efficient approach to guide immunotherapy. Additionally, cuproptosis is a recently identified regulated cell death program that is triggered by copper ionophores. However, its possible significance in tumor immune cell infiltration is still unclear.MethodsCuproptosis subtypes in HCC were identified using unsupervised consensus cluster analysis based on 10 cuproptosis regulators expressions, and a cuproptosis-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…Since the discovery of cuproptosis, the role of cuptoptosis in liver cancer prognosis and TME has been gradually evaluated. Previous studies mainly explored this issue by constructing Lasso cox model, which directly entered the target genes as model inputs (47)(48)(49)(50)(51)(52)(53). The Lasso model is applied to analyze multicollinearity data (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of cuproptosis, the role of cuptoptosis in liver cancer prognosis and TME has been gradually evaluated. Previous studies mainly explored this issue by constructing Lasso cox model, which directly entered the target genes as model inputs (47)(48)(49)(50)(51)(52)(53). The Lasso model is applied to analyze multicollinearity data (54).…”
Section: Discussionmentioning
confidence: 99%
“…Next, we assessed the drug-sensitivity of CRFCS in HCC by applying the R package of "pRRophetic". By analyzing data from TCGA, we found that the high CRFCS group had a lower IC 50 sorafenib compared with the low CRFCS group (Figure 6A). To verify these results, an external data from ICGC-LIHC-US was analyzed which confirmed that the high CRFCS group are more sensitive to sorafenib (Figure 6B).…”
Section: Crfcs and Drug-sensitivitymentioning
confidence: 99%
“…It leads to the aggregation of lipoacylated proteins and the loss of iron-sulfur cluster proteins, which may ultimately result in cell death due to toxic effects ( Tsvetkov et al, 2022 ). These findings suggest a novel perspective for investigating the application of cuproptosis in cancer treatment ( Wang et al, 2022a ).…”
Section: Introductionmentioning
confidence: 87%
“…We compared our own model to 12 other published HCC prognostic models to better show its predictive power (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Multivariate analysis was used to calculate the risk value and prognostic evaluation for each dataset, leveling the playing field amongst the four models.…”
Section: New Model As a New Predictor Of Hccmentioning
confidence: 99%